Core outcome set for gene therapy in haemophilia: Results of the coreHEM multistakeholder project. Issue 4 (20th May 2018) - Iorio, A.; Skinner, M. W.; Clearfield, E.; Messner, D.; Pierce, G. F.; Witkop, M.; Tunis, S.; ,
Abstract : Background: Gene therapy trial results show potential to cure haemophilia A and haemophilia B. Securing broad access to a cure for a lifelong chronic disease is anticipated to face barriers at the individual and healthcare system levels, which can be partly mitigated by harmonized planning of clinical research studies. The aim of the coreHEM project was to determine the set of outcome measures required to evaluate efficacy, safety, comparative effectiveness and value of gene therapy for haemophilia. Methods: Modified Delphi consensus process, based on methods adapted from the COMET Initiative. Results: Forty‐nine participants (five patients, five clinicians, five researchers, four regulators, three research agencies, six health technology assessors, nine payers and 12 drug developers) took part in the study, with over 90% participation. The frequency of bleeds, factor activity level, duration of expression, chronic pain, healthcare resource use and mental health were identified as the core outcomes to be measured in addition to regulatory‐mandated adverse effects. Conclusions: For the first time in haemophilia, a core outcome set has been developed, with the involvement of representatives of all relevant stakeholder groups. The core set has been expanded to include outcomes supporting assessment of comparative effectiveness and value, with the goal of streamlining regulatory approval, health technology assessment and market access decisions. Patient involvement ensures that outcomes are meaningful and relevant to those living with haemophilia. Active dialogue among drug developers, regulators and payers throughout the process is expected to facilitate broad uptake of the core outcomes in forthcoming clinical trials.